Anaerobic bio-digestion of concentrate obtained in the process of ultra filtration of effluents from tilapia processing unit - Souza, Milena Alves de [UNESP]; Chaguri, Milena Penteado [UNESP]; Castelini, Fabrício Rogério [UNESP]; Lucas Junior, Jorge de [UNESP]; Vidotti, Rose Meire (Sociedade Brasileira de Zootecnia, 2012)
The objective of the present study was to evaluate the efficiency of the process of biodigestion of the protein concentrate resulting from the ultrafiltration of the effluent from a slaughterhouse freezer of Nile tilapia. Bench digesters were used with excrements and water (control) in comparison with a mixture of cattle manure and effluent from the stages of filleting and bleeding of tilapias. The effluent obtained in the continuous process (bleeding + filleting) was the one with highest accumulated population from the 37th day, as well as greatest daily production. Gases composition did not differ between the protein concentrates, but the gas obtained with the use of the effluent from the filleting stage presented highest methane gas average (78.05%) in comparison with those obtained in the bleeding stage (69.95%) and in the continuous process (70.02%) or by the control method (68.59%).
Keywords: biogas; bleeding; filleting; freshwater-fish; methane